Lateral mobilization of soil carbon induced by runoff along karstic slopes. (15th April 2020) - Gaspar, Leticia; Mabit, Lionel; Lizaga, Ivan; Navas, Ana
Abstract: Soil erosion induced by runoff is a main hydrological pathway for lateral transport of carbon in terrestrial landscapes. More information about how water erosion influences the carbon gains and losses at different erosional and depositional landform positions is critical, especially in fragile agroecosystems with a variety of land uses and ephemeral hydrological and sedimentological pulses, typical of Mediterranean environments. The purpose of this study is to characterize the lateral mobilization of soil organic and inorganic carbon (SOC and SIC) along topographically driven transects over a period of four decades in a sub-humid karstic area in northern Spain. The 137 Cs inventories and the characterization of terrain attributes of the study area were used to identify whether erosional or depositional processes have been predominant in the 58 sampling sites. Average soil losses and gains varied between −4 and +4 mm ha −1 yr −1, and the carbon patterns obtained are discussed in the context of the dominant hydrological processes in the study area. Results indicate that SOC and SIC losses were related to an increase in water flow accumulation, while the highest SOC gains were recorded at concave positions. Soil erosion processes and the content of SOC and SIC in soils are the two main factors controlling carbon budgets. The topographical and geomorphological characteristics of the transects, the spatial distribution of land uses and the presence of landscape linear elements such as terraces or paths, affect runoff and determine the sediment connectivity and carbon dynamics along the slopes. The combined use of 137 Cs and the perceptual model provides reliable SDR estimates benefiting the appraisals of the redistribution of eroded carbon. The knowledge of processes involved in the lateral carbon movement induced by runoff along karstic hillslopes provides a better understanding of the role of soil erosion as carbon source or sinks in the global carbon cycle. Graphical abstract: Image 1041 Highlights: 137 Cs inventories document gain or loss of soil by water erosion on karstic slopes. Perceptual approach illustrates SOC and SIC lateral movement along five transects. Topography and landscape linear elements affect runoff and sediment pathways. Erosion-induced SOC loss depends on erosion rates and topsoil SOC content. SIC patterns depends on pedogenesis besides soil mobilization.